A Method for Identifying Pollution Sources of Heavy Metals and PAH for a Risk-Based Management of a Mediterranean Harbour. (14th November 2017) - Paladino, Ombretta; Moranda, Arianna; Seyedsalehi, Mahdi
Abstract : A procedure for assessing harbour pollution by heavy metals and PAH and the possible sources of contamination is proposed. The procedure is based on a ratio-matching method applied to the results of principal component analysis (PCA), and it allows discrimination between point and nonpoint sources. The approach can be adopted when many sources of pollution can contribute in a very narrow coastal ecosystem, both internal and outside but close to the harbour, and was used to identify the possible point sources of contamination in a Mediterranean Harbour (Port of Vado, Savona, Italy). 235 sediment samples were collected in 81 sampling points during four monitoring campaigns and 28 chemicals were searched for within the collected samples. PCA of total samples allowed the assessment of 8 main possible point sources, while the refining ratio-matching identified 1 sampling point as a possible PAH source, 2 sampling points as Cd point sources, and 3 sampling points as C > 12 point sources. By a map analysis it was possible to assess two internal sources of pollution directly related to terminals activity. The study is the prosecution of a previous work aimed at assessing Savona-Vado Harbour pollution levels and suggested strategies to regulate the harbour activities.